Potassium-containing hydroxylated hydrotalcite as efficient catalyst for the transesterification of sunflower oil - Benedictto, German P. (2018)
Different hydrotalcite-based materials were evaluated as heterogeneous catalysts for the transesterification of sunflower oil with methanol. A set of compounds based on magnesia-alumina structures (MgAl hydrotalcites) were synthesized. To carry out the initial co-precipitation, salts and bases of either sodium or potassium were chosen. The products obtained were afterward submitted to calcination and dehydration/rehydration treatments in order to induce layered restoration. The intermediate and final solids obtained were characterized by XRD, FTIR, SEM and EDX analyses. The catalytic activity of the rehydrated samples was tested in the transesterification reaction of sunflower oil with methanol for biodiesel production. The effectiveness of these materials as heterogeneous catalysts was evaluated in terms of time for maximum conversion and reusability. All the products were identified as hydrotalcite-like materials being accompanied by small percentages of crystalline Mg phases when potassium ions were used for providing the alkaline synthesis medium.; Improved conversion levels were obtained by using K-containing MgAl hydrotalcites submitted to calcination at 500 °C and subsequently rehydrated under controlled conditions. The presence of residual sodium or potassium was detected in the rehydrated samples, in concordance with the corresponding cation used for the starting synthesis formulation. Both materials were catalytically active, the better results being those reached with the potassium-containing samples. Conversion as high as 80% of biodiesel was obtained at a methanol/oil mass ratio of 3:10, a catalyst concentration of 3% w/w referred to the oil mass and 65 ± 1 °C for 180 min of reaction time. After reactivation, the catalyst was reused giving 40% oil conversion after 300 min of reaction time.